State-Space Models on the Stiefel Manifold with a New Approach to Nonlinear Filtering - Yukai Yang; Luc Bauwens (Econometrics, 2018)
We develop novel multivariate state-space models wherein the latent states evolve on the Stiefel manifold and follow a conditional matrix Langevin distribution. The latent states correspond to time-varying reduced rank parameter matrices, like the loadings in dynamic factor models and the parameters of cointegrating relations in vector error-correction models. The corresponding nonlinear filtering algorithms are developed and evaluated by means of simulation experiments.